1971
DOI: 10.1073/pnas.68.7.1441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rifampicin and Two of Its Derivatives on Cells Infected With Moloney Sarcoma Virus

Abstract: It is shown that rifampicin, and especially the related antibiotic 2',6'-dimethyl-N(4')-benzyl-N(4')-[desmethylirifampicin (DMB-rifampicin) can inhibit focus formation by Moloney sarcoma virus on BALB/3T3 tissue cultures. At 10 ug/ml DMB-rifampicin totally inhibits focus formation while reducing virus replication by at least a factor of fifty and cell proliferation by only a factor of three. These observations, taken together with those of others, suggest a role for an RNA-dependent DNA polymerase and the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The benzyl derivatives of rifampicin AF/ABDMP was reported to inhibit cell transformation by MSV (9). Those 3-amine derivatives most active against the viral DNA polymerase inhibited MSV-induced cell transformation by 90-100%0 and 30-100% at concentrations of 10 ug/ml and 5 ;Lg/ml, respectively (Data with six of these are given in Those seven derivatives that inhibit both viral polymerase and cell transformation were tested against a partially purified DNA polymerase derived from human KB cells (Fig.…”
Section: -Amine Derivatives Of Rifamycin-sv Inhibit Cell Transformatmentioning
confidence: 99%
“…The benzyl derivatives of rifampicin AF/ABDMP was reported to inhibit cell transformation by MSV (9). Those 3-amine derivatives most active against the viral DNA polymerase inhibited MSV-induced cell transformation by 90-100%0 and 30-100% at concentrations of 10 ug/ml and 5 ;Lg/ml, respectively (Data with six of these are given in Those seven derivatives that inhibit both viral polymerase and cell transformation were tested against a partially purified DNA polymerase derived from human KB cells (Fig.…”
Section: -Amine Derivatives Of Rifamycin-sv Inhibit Cell Transformatmentioning
confidence: 99%
“…Two rifampicin derivatives, dimethylbenzylrifampicin (DMB) and rifazacyclo-16, inhibit viral reverse transcriptase (7) and at comparable concentrations also inhibit murine sarcoma virus (MSV) transformation of mouse cells in tissue culture (10)(11)(12)(13)(14). This correlation between biological and biochemical data suggests that these drugs block transformation by inhibiting the viral induced reverse transcriptase; alternatively the drugs may inhibit other cellular enzymes required for transformation.…”
Section: Introductionmentioning
confidence: 90%
“…Previous reports (10,13,17) showed that DMB inhibited murine leukemia virus transformation of the mouse cell line UC1-B without the addition of amphotericin B, although it was subsequently shown that the inhibition was more reproducible and more complete when the amphotericin B was included (11). It was hypothesized that amphotericin B acted by altering cell membrane permeability, thus enabling the DMB to be taken up more readily by the cells.…”
mentioning
confidence: 99%
“…One of the rifampicin derivatives, 2',6'-dimethyl-N(4')-benzyl-N(4') [desmethyl]rifampicin, inhibited focus formation and infectious virus production in BALB/3T3 cells by Moloney Sarcoma Virus (1,2). It also inhibited Moloney leukemia virus-induced focus formation in the UC1-B cell line derived from BALB/3T3 cells (3a, 3b).…”
mentioning
confidence: 95%